Molecular characterization and subtype analysis of Blastocystis sp. in captive wildlife in Henan, China - Cui Zhaohui; Huang Xiyao; Zhang Sulan; Li Kaifang; Zhang Aili; Li Qichen; Zhang Yutong; Li Junqiang; Qi Meng (Parasite)
Blastocystis sp. is a zoonotic intestinal protozoan that is ubiquitous globally, residing in the gastrointestinal tracts of both humans and various animals. In the present study, a PCR-sequencing tool based on the SSU rRNA gene was employed to investigate the prevalence and subtypes of Blastocystis spp. in 204 fresh fecal samples collected from 20 captive wildlife species from a bird park in Henan Province, Central China. Overall, Blastocystis was present in 13.73% (28 out of 204) of the samples and 25% (5 out of 20) of the species. A total of four zoonotic subtypes of Blastocystis sp. were found: ST1, ST3, ST5, and ST27, with the latter being the most prevalent, accounting for 35.71% (10 out of 28) of the 5 species positive for Blastocystis sp. To the best of our knowledge, this is the first report of Blastocystis ST27 in birds in China, namely bar-headed goose (Anser indicus) and peafowl (Pavo muticus). The data suggest that captive wildlife, particularly those in bird parks, may frequently be infected with this zoonotic pathogen. Consequently, these animals may serve as potential reservoirs for zoonotic infections in humans.